Communication in Collaborative Leadership in the Corporate Social and Environmental Responsibility Forum in Wajo Regency - Amran, ‎; Hasniati, ‎; Sultan, M. Iqbal (KnE Social Sciences, 2025)
This study aims to thoroughly examine the role of communication in building and strengthening collaborative leadership within the Corporate Social and Environmental Responsibility Forum (TJSLP) of Wajo Regency. The TJSLP Forum serves as a strategic platform that brings together stakeholders from government, private sector, and community organizations to collaborate in designing and implementing social and environmental programs. Using a qualitative approach and case study method, data were collected through in-depth interviews, participatory observation, and analysis of official forum documents. The findings indicate that effective, participatory, and transparent communication plays a crucial role in building trust, enhancing stakeholder engagement, and improving the effectiveness of collaborative leadership. Communication within the forum is conducted through open dialogues, deliberations to achieve consensus, and equitable sharing of information and resources. Identified challenges include differences in interests, information asymmetry, and limited communication capacities among actors. Nevertheless, the application of adaptive communication strategies and the strengthening of interpersonal capacities have successfully minimized potential conflicts and fostered mutual understanding. This study asserts that collaborative leadership based on strategic communication is a key factor in supporting the successful implementation of TJSLP programs at the regional level. The implications of these findings are significant not only for the management of TJSLP, but also contribute conceptually to the development of collaborative leadership theory in the context of sustainable development governance.